Karawitan Composition “Catra Patra” | Komposisi Karawitan “Catra Patra” - Ananta Kusuma; Tri Haryanto (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
Catra Patra is a creation of percussion percussion using the gamelan Semara Pagulingan Saih Pitu as a medium of expression. The theme raised in this work is beauty, this theme is chosen because tedung has various kinds of beautiful ornaments, the theme is adjusted to the structure of the work so that it can become a unified whole, the theme is adapted to the structure of the claim so that it can become a single unit. intact. This work is divided into three stages which are taken from the concept of Alma M. Hawkins in the book Creating Trough Dance that the arrangement of a work of art is achieved through 3 stages, namely exploration, improvisation, and forming. These three stages are applied in the process of cultivating the percussion percussion created by Catra Patra. The purpose of writing the composition of the composition of the percussion created by Catra Patra is to convey the author's ideas to the community. The form and structure of this work consists of three basic concepts, namely tri angga (head, body, and feet), the head in this case is called pengawit, the body is the crew, while the feet are pushers. In each section there is a connector/transition (penyalit) that supports beauty to become a unified whole, in the third section it is formed from several patterns such as gineman, kekebyaran, bapang, and gegenderan.